PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA VARIO DI LUBUK SIKAPING - Yurasti, Yurasti; Oktaviani, Tia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Purchase decisions are based on the knowledge that consumers get based on information so that consumers are sure of the goods or services needed. This research aim to prove how advertising influence and brand image to purchase decision. Reseach was conducted in Lubuk Sikaping and the populationin this study are consumer who had used of Honda Vario Motorcycles . The research sample consisted of 100 respondent. The data collection methods were Observation, Interview, Documentation and Questionnaire. Data are analyzed using multiple linear regression. The result showed that partially advertising has a significant effect on the Purchase Decision of Honda Vario Motorcycle, with a significant value of 0.001 < alpha 0.05. Brand Image does not have a significant effect on Purchase Decisions for Honda Vario Motorcycles with a significant value of 0.130 > alpha 0.05. Advertising and Brand Image gave significant effect on the Purchase Decisions for Honda Vario Motorcycles simultaneously by the significant value of 0.000 < alpha 0.05.Keywords: Advertising, Brand Image, Purchasing decision.